OPTIMIZING THE PERCEPTION OF REALITY AS A PRECURSOR FOR HUMAN EVOLUTION; AUGMENTING AND MIXING INFORMATION DOMAINS IN A SINGLE STREAM OF COGNITION - Kokins, Aigars (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Human vision is like a set of pictures moving through time. By analyzing individual frames, it is possible to find spaces of lower and higher priority, distant views and closely located objects. Regions of perceivable space are easily modifiable so that one can individually customize what one sees. Head mounted display technology, currently under development, allows for the modification of our vision, thus replacing the visible world with the artistically imagined or overlaying real time data over perceivable space. The future of perception omits distance – allowing contextual data to come through our vision, providing a digitally controlled perception system in a place of our natural one.